After the Long Wait: Post-Migrant Agency and the Politics of Return in Tahar Ben Jelloun's A Palace in the Old Village. Issue 2 (August 2018) - Bugeja, Norbert
Abstract : This essay offers a contemplation of the affinity between a post-literary idiom and the question of migrant writing through a reading of Tahar Ben Jelloun's novella A Palace in the Old Village (Arcadia Books, 2011 [2009]). Taking its cue from the novella's account of its Maghrebi protagonist, the migrant worker Mohammed, in the moment of his retirement and return to Morocco, the essay opens up the question of whether the liminal 'Franco-Maghrebi borderland' (Sajed 2013 ) which he traverses, as well as the home-space itself, may be perceived as either discursively generative and liberatory spaces, or as ultimately aporetic zones of living. The essay evaluates Ben Jelloun's novella as a 'post-migrant' one, approaching the narrative spatial projection back into the native space as a dynamics of refraction, a quest for 'choric' (Rickert 2007 ) spatiality, and a restitution of agency to and from the autochthonous. The essay finally suggests that Ben Jelloun's novella stages an amplified visualisation of post-migrant discourse as it percolates through the migrant body. As Mohammed deteriorates on his native Moroccan terrain, waiting for his children who never show up, his fading body is now indelibly marked by the labour to which post-war Europe owed much of its economic resurgence: a dynamics which is described here as a 'refracted indigeneity'.